Modeling and simulation of the International Space Station (ISS) electrical power system. (16th June 2021) - Kuzlu, Murat; Abalos, Kyle; Elma, Onur; Popescu, Otilia; Pipattanasomporn, Manisa
Summary: The International Space Station (ISS), launched on 20 November 1998, is the largest manmade structure orbiting the Earth. It is one of the most complicated systems providing a scientific laboratory environment to conduct scientific experiments within the space environment for further space explorations. It also provides a comfortable and safe place for astronauts to operate the station. In this study, the modeling and simulation of the ISS's electrical power system have been conducted in MATLAB/Simulink. It provides a virtual environment to emulate the ISS electric power system. This virtual environment allows the evaluation of different load management algorithms for ISS to enhance its energy sustainability. In addition, the paper presents a load management algorithm for managing ISS operations and its impact on the battery state of charge (SoC) at various photovoltaic (PV) generation percent factors, that is, 50%, 75%, and 100%. The simulation results indicate that the proposed load management algorithm can improve the performance of battery SoC up to 13%. Abstract : This study provides a virtual environment in MATLAB/Simulink, which allows researchers and engineers to emulate the ISS's electrical power system and evaluate various algorithms for managing energy sources and loads to enhance energy sustainability in the space environment. It also presents a load management algorithm for managing ISS operations. The impact of the proposed algorithm on the state of charge (SoC) is also investigated under reference values of the PV generation percent factors.